1995
DOI: 10.1021/om00012a038
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Reductive Elimination from Disubstituted Aryl Hydride Complexes: Mechanistic and Thermodynamic Considerations

Abstract: The complexes (C5Me5)Rh(PMe3)(3,5-C6H3R2)H for R = C(CH3)3, CH(CH3)2, Si(CH3)3, CH3, and CF3 (lc-g) have been prepared both by irradiation of (C5Me5)Rh(PMe3)(C2H4) in neat arene and by thermolysis of (C5Me5)Rh(PMe3)(Ph)H (la) in neat arene. Quenching the hydride species with CHBr3 allowed isolation of the corresponding bromide complexes (CsMe5)Rh(PMe3)(3,5-C6H3R2)Br (2c-g). Rates of reductive elimination of arene for the series of disubstituted aryl hydride complexes were measured at various temperatures and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Therefore, the attempt on direct formation of styrene from benzene and ethylene using aromatic C-H bond activation leading to C-C bond formation is a considerably attractive field, which has enough room to be developed from the industrial point of view. As described in Section 1, much work related to homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Group VIII metal complexes can also be employed for olefin oxidation reactions such as Pd-catalyzed partial oxidation of ethylene, as is done in the well-known Wacker reaction to form acetaldehyde [61,62] and oxidative vinylation of acetic acid to produce vinyl acetate [63].…”
Section: Conventional Synthesis Of Styrenementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the attempt on direct formation of styrene from benzene and ethylene using aromatic C-H bond activation leading to C-C bond formation is a considerably attractive field, which has enough room to be developed from the industrial point of view. As described in Section 1, much work related to homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Group VIII metal complexes can also be employed for olefin oxidation reactions such as Pd-catalyzed partial oxidation of ethylene, as is done in the well-known Wacker reaction to form acetaldehyde [61,62] and oxidative vinylation of acetic acid to produce vinyl acetate [63].…”
Section: Conventional Synthesis Of Styrenementioning
confidence: 99%
“…Significant efforts have been directed at homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, among the numerous stoichiometric studies, relatively small numbers of organic syntheses are reported.…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases the reductive elimination is so kinetically and thermodynamically favorable that it was impossible to observe the intermediate hydride cluster. On the contrary, a series of mono-and binuclear transition metal complexes containing hydride and alkyl (aryl) ligands were isolated and studied in detail because of their importance for understanding the mechanisms of catalytic activation of the hydrocarbon C-H bond, see for example [21][22][23][24][25][26][27][28][29][30][31][32]. Some particularly stable cis ''hydride-aryl'' complexes of ruthenium [33], iridium [34][35][36], platinumtungsten [37] dimers, [Me 2 Si]-ansa-bridged permethylmetallocene systems [22,24,38] allowed X-ray crystallographic study.…”
Section: Introductionmentioning
confidence: 99%
“…subsequent reactions of this cationic methyl derivative with dihydrogen and with isocyanides are outlined in equations (25) and (26). The coupling of the methyl group with…”
mentioning
confidence: 99%
“…• C occurs at osmium to form (26). On warming, the methyl group migrates to osmium via an intermediate in which the hydride ligand bridges both metals, methane is eliminated, and the resulting coordinatively unsaturated osmium atom undergoes oxidative addition of an o-C-H bond of one DPPM phenyl group to yield (27).…”
mentioning
confidence: 99%